Obese women's reasons for not attending a weight management service during pregnancy. (5th July 2013) - Olander, Ellinor K.; Atkinson, Lou
Abstract: Evaluations of services targeting obese women's gestational weight gain often report low uptake. Thus it is important to elicit the reasons why obese pregnant women decline to participate in these services and to identify their barriers to participation. Sixteen obese pregnant and postnatal women were interviewed regarding their reasons for declining a group‐based service targeting their gestational weight gain. All interviews were recorded, transcribed verbatim and analyzed thematically. Both pragmatic and motivational barriers were identified. The most common practical reasons for not attending the service were its inconvenient location and time, and feeling unable to attend due to work commitments. Pregnancy‐specific barriers included decreased mobility and feeling unwell. Motivational barriers included lack of interest and not wanting to focus on one's weight in pregnancy. These findings highlight issues that need to be taken into consideration when designing group‐based weight management services for this population.